Implementing the BBOK package via auricular acupressure and health education to reduce weight and BMI in adolescents with obesity: An evidence-based nursing report - Istiqomah Istiqomah; Syamsul Anwar; Ninik Yunitri (Indonesian Nursing Journal, 2026)
Background: Adolescent obesity is a growing health concern with physical and psychological complications. This Evidence-Based Nursing Practice (EBNP) analyzed the effectiveness of the BBOK (Optimal Body Weight) package, combining auricular acupressure and health education, in reducing body weight (BW) and body mass index (BMI) among adolescents with obesity. Methods: Using an EBNP approach, auricular acupressure and health education interventions were implemented over six weeks. Nine adolescents aged 13–19 years with obesity from RW 01, 02, and 05, Rawasari Village, Cempaka Putih District Health Center, were selected based on inclusion criteria. Interventions included health education on obesity, nutrition, physical activity, sleep, and stress management, plus auricular acupressure using vaccaria seeds at the hunger point. Evaluations measured BW, BMI, and knowledge, attitudes, and behaviors before and after intervention. Results: Paired Sample T-Test analysis showed significant reductions in body weight (MD = 0.68; p = 0.000) and BMI (MD = 0.25; p = 0.000). Significant improvements were also observed in knowledge (MD = 4.78; p = 0.000), attitudes (MD = 2.44; p = 0.026), and healthy behaviors (MD = 10.67; p = 0.000). Conclusion: The BBOK package was associated with significant improvements in body weight, BMI, and healthy lifestyle behaviors among adolescents with obesity. While these findings suggest potential as a community nursing strategy, the modest magnitude of weight and BMI reduction, small sample size, and absence of a control group warrant cautious interpretation. Further controlled studies are needed to validate these findings.